Determinants of dividend policy of foreign listed companies on Karachi Stock Exchange - Khan, Faisal (INSInet Publications, 2011)
This paper reports the empirical findings of a questionnaire survey about corporate dividend policy addressed to finance directors of foreign listed companies listed on Karachi stock exchange. We survey 60 foreign listed companies and the questionnaire is asked from their finance directors like earlier studies (for example, Brav et al ., 2005 in the US and Dhanani, 2005 in the UK) in order to visualize their view and understanding about the dividend decision. Our survey resulted into some very important points to be noted. The dividend decision is influenced by market price of share, dividend growth and smoothening of dividend. The firms give importance to the dividend as it was in past and the growth is considered at time of declaration of dividend. The alternative of dividend is investment consideration and the firms always issue dividend to attract the retail investors at top priority. Rather than reducing dividends, the firms would raise new funds to undertake investments. The dividend decision is influenced by the competitor policy and the fear of signaling of shortage of profitable investment. The results demonstrate that foreign listed companies are more concerned with dividend policy.